(3GdEHOGY aj GJNGP GdbQGQGJ GdGOGQjI (B/s - (3GdaVd, eDjO YHO GdMSjfs ((3YeGf(B: s (3GKQGA ddfTQ(B, s, 2009)
(3JCWjQ eaGgjej h efWdbGJ acQjI Mhd GdGHOGY , GJNGP GdbQGQGJ GdGHOGYjI , GdGMJeGdGJ h GdJhRjYGJ GdGMJeGdjI aj OYe GdbQGQ GdGHOGYj , GdGHOGY aj JWHjb GdHQeLI GdNWjI dGSJZdGd GdehGQO , GdGHOGY aj JMdjd GdbQGQ , JUeje TLQI GdbQGQ hab efXhQ EHOGYj , GdGHOGY aj GSJNOGe fXdQjI GdefaYI aj GJNGP GdbQGQGJ (B.s
(3edGMb U(B.341s
Keywords: (3GJNGP GdbQGQGJs; (3EOGQI GdCYeGds; (3GdEHJcGQs